STANDARIZE OF SIMBOL AND SYSTEM USING MEDICAL RECORD DOCUMENTS OF INPATIENT PATIENTS IN RSJD Dr. ARIF ZAINUDIN SURAKARTA - Warsi Maryati; Aris Octavian Wannay (Asosiasi Perguruan Tinggi Rekam Medis dan Informasi Kesehatan Indonesia- APTIRMIKI, 2017)
The accreditation agency in Indonesia is the Hospital Accreditation Commission (KARS). Since 2012, one of the chapters in the KARS accreditation standard is the Communication and Information Management (MKI) chapter in the hospital management group. Based on a preliminary study at RSJD Dr. Arif Zainudin Surakarta has been accredited plenary but has not done monitoring. The purpose of this study was to evaluate the accreditation standards of MKI 13 on the Medical Record Document of Inpatient in RSJD Dr. Arif Zainudin Surakarta in 2017. The research method used is descriptive research type, cross sectional approach, data collection using observation and interview, sampling technique used is quota sampling. Data processing in this research include collecting, editing, coding, classification, tabulating, and data presentation. The results of this study indicate that the percentage of symbols used 78.7% is not standardized, the abbreviation used is 71.2% standardized. Standardization of symbols and abbreviations based on the manual set by the Director of the Hospital with the title of the book